PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI - Anshori, M. Isa (Fakultas Ekonomi, UIN Maliki Malang, 2011)
Quality of work life is a level where members of an organization is able to satisfy important personal needs through his experience in doing the job in the organization. As well as the high commitment of the employees at the organization's employees will exert all their ability to perform all tasks assigned to them, including obey all the rules. Based on the comparison of t-values calculated by t-table where the t-calculated value was greater than the value of t-table then H0 refused and H1 accepted, meaning that independent variable compensation, job design, participation and job security partially have a significant effect on Insurance employees' organizational commitment